MENANAMKAN NILAI NILAI KEJUJURAN DI DALAM KEGIATAN MADRASAH BERASRAMA (BOARDING SCHOOL) - Messi, Messi; Harapan, Edi (Graduate Program Magister Manajemen Pendidikan, 2017)
Basically, education is the process of cultural inheritance from the former generation to the younger ones. One of the core values of character that must be instilled to the students is the value of honesty. Boarding school is a mean to instill honesty value for student. The purpose of this study was to find out how big the effort of MAN 3 Palembang in fostering the value of honesty for student through boarding school activities was. This research used descriptive qualitative approach. This research was conducted in MAN 3 Palembang. Data collection techniques used to obtain data in this study were observation, interviews, documentation. The result showed that the planting of honesty value in MAN 3 Palembang consists of several coaching activities (1) activity of faith building and piety to God Almighty, (1) enforcement of discipline. The coaching of the value honesty is implemented through several strategies and approaches as follows: (1) integration of honesty and ethics values in boarding school activities, (1) internalization of honesty values embedded by all students (3) training, (4) giving examples, (5) creating an atmosphere of character in the boarding school, and (6) the culture of honesty in the boarding school. The program implementation of the value honesty in accordance with the book order boarding. In addition, the value of honesty has appeared on the activities in the boarding school MAN 3 Palembang